Comedy Central stand-up vault. 2 [videorecording (DVD)]. - Attell, Dave; Birbiglia, Mike; Caliendo, Frank, 1974-; Galifianakis, Zach; Lynch, Stephen, 1971-; Oswalt, Patton, 1969-; Swardson, Nick; Tosh, Daniel, 1975- (Paramount Pictures, 2015)
An exciting collection of some of the most hilarious stand-up comedians of all-time!